POTENTIAL CHITOSAN OF WASTE SHELL MANTIS SHRIMP (Harpiosquilla raphidea) AS ANTIBACTERIAL - Putra, Muhammad Ridho; Karnila, Rahman; Hasan, Bustari (Asian Journal of Aquatic Sciences, 2023)
Mantis shrimp carapace waste can be processed into chitin and chitosan as antibacterial. This study aims to determine the characteristics, and heating time of chitosan on the potential of chitosan as an antibacterial, and to obtain the best chitosan in increasing the durability of catfish meatballs. Experimental research method with the manufacture of chitin and continued with deacetylation with a long heating time to obtain chitosan. The analytical parameters consisted of chemical characteristics (moisture content, ash, and degree of deacetylation), the inhibitory power of chitosan against Escherichia coli and Staphylococcus aureus bacteria, and the effectiveness of chitosan on the quality of catfish meatballs. The results showed that the chemical characteristics of chitosan were water content (K1 3.72%, K2 4.65%, K3 5.24%), ash (K1 2.38%, K2 2.53%, K3 3.69%), and the degree of deacetylation (K1 54.31%, K2 78.04%, K3 79.51%). The results of the inhibition test of chitosan against Escherichia coli and Staphylococcus aureus bacteria using the well method showed an inhibition zone with values (K1 10.11 mm and 10.18 mm, K2 11.52 mm and 11.48 mm, K3 12.15 mm and 11. 70 mm, positive control 14.64 mm and 14.02 mm, negative control 9.25 mm and 7.35 mm). This value indicates that the activity of chitosan as an antibacterial is quite strong. The effectiveness of chitosan on the quality of catfish meatballs with 7% chitosan immersion and storage at room temperature showed that the TPC value of catfish meatballs with chitosan could prolong the shelf life of meatballs until day-2.